PENGARUH SUBSTITUSI TEPUNG IKAN DAN TERI DALAM PAKAN TERHADAP EFISIENSI PEMANFAATAN PAKAN DAN PERTUMBUHAN BENIH IKAN NILA (Oreochromis niloticus) - Subandiyono Subandiyono; Pinandoyo Pinandoyo; Ratih Wulandari (Sains Akuakultur Tropis : Indonesian Journal of Tropical Aquaculture, 2019)
The growth of tilapia could be improved when the feed utilization by the find was more efficien.Dietary anchovy flour might increase the utilization rate the feed. Feedswith amino acid profile similar to the amino acid profile of the fish would growth better. However, the feed lack of one might essential amino acids might disrupt the process of  growththe fish. The feed substitution could improve better amino acid congfiguration for better growth of fish. This experiment was to determine the effect of substitution of anchovy flour with fish meal in feed onthe feed utilization efficiency and growth of tilapia (O. niloticus) seed. The trial fish used were individual body better range betwen 5-7 cm tilapia (O. niloticus) with initial average body weight of 3.07±0.03 g/fish density the was 1 fish/liter for 35 days. The variables measured included the totalfeed consumption (TFC), feed utilization efficiency (FUE), protein efficiency ratio (PER), relative growth rate (RGR), and survival rate (SR). The experimentused was completely randomized design that consisted of 5 treatments and 3 replicates. The fifth treatments were treatment A, B, C, D, and E, withration of dietary fish meal to anchovy flour was 0:100, 25:75, 50:50, 75:25, and 100:0%, respectively. The data showed that dietary anchovy flour resulted significantly effect on TFC, FUE, RGR, and PER values, but did not for SR value.  Treatment Cassumsted the best performance values for TFC,FUE, PER, and RGR, with the values for 80,70%, 69,45%, 2,19%, and 1,6%/day, respectively. The water quality parameters during this study varried between suitable range for the  tilapia (O. niloticus).  It was suggestedthat substitution of fish meal to anchovy flour with the ration of 50:50% in feed was able to increase the values of TFC,FUE, PER, and RGR.